Non-Governmental Organisations (NGOs) Role in Driving Urban Climate Governance: The Case of CIKOD and GAYO in Ghana - Ama Kissiwah Boateng (European Scientific Journal, ESJ, 2022)
While cities are considered pivotal sources of global greenhouse gas emissions, they are also essential in urban climate governance. The role of NGOs in different contexts is increasing in terms of the mode of governance, but the empirical evidence of how they contribute to urban climate action in small and medium-sized cities, especially in developing countries is limited. Drawing evidence from Ghana, a case study research design was adopted and this facilitated an in-depth understanding of how NGOs contribute to urban climate governance in small and medium-sized cities in Ghana. The primary data collection methods included key informant interviews with two purposively selected NGOs: the Center for Indigenous Knowledge and Organisational Development (CIKOD) and the Green Africa Youth Organisation (GAYO), which is located in the Wa Municipality and the Cape Coast Metropolis respectively. Randomly selected residents made up of chiefs and assembly members, who are the representatives of the people in the municipality, were interviewed. All interviews were transcribed and analysed in generated themes. The study revealed that climate change adaptation actions included local empowerment through capacity building, climate advocacy, and waste management. As a result of the adaptation focus, the paper concludes that collaborations and partnerships among state and non-state actors will help generate greater resilience benefits for local communities. Climate change adaptation programmes, which are often initiated by NGOs, are also steered by local residents outside of administrative systems.